Factors promoting gender-responsive early childhood education: The Peruvian case - Arroyo-Corahua, Luz Fernanda; Ruiz-Ruiz, Marcos Fernando (Revista de Ciencias Sociales, 2023)
Gender differences become relevant in the educational sphere for the construction of a sustainable society. Therefore, this research aimed to determine the factors that promote the Peruvian gender-responsive early childhood education system (3-5 y/o). Based on an exploratory and descriptive design, a qualitative structural analysis was carried out with the help of a panel of five expert educators, with early childhood education children (3-5 years old) in Peru as the context of the study. Using the Matrix-based Multiplication Applied to a Classification tool, we found the identification of the following key factors of the system: the implementation of policies, teacher training, pedagogical practices, the choice and characteristics of teaching resources, as well as the expectations of families regarding early childhood development with a gender approach. The leadership rests mainly with the Peruvian Ministry of Education, which is responsible for forming an egalitarian society from a comprehensive approach. Any strategic planning effort must address this problem of Peruvian early childhood education from a holistic perspective. This study is a starting point for studying future scenarios for the education system in the medium and long term.